KARAKTERISTIK SIFAT FISIKA BRIKET ARANG TEMPURUNG KELAPA DAN TONGKOL JAGUNG - Wulandari, Febriana Tri; Lestari, Dini; Fahrussiam, Fauzan; Ningsih, Rima Vera; Raehnayati, Raehnayati (JURNAL HUTAN LESTARI, 2024)
Agricultural waste needs to be processed into products that provide benefits by making alternative fuels in the form of biobriquettes (charcoal briquettes). The purpose of this study was to determine the best composition of charcoal briquettes from coconut shell waste and corn cobs by testing charcoal briquettes in order to obtain quality charcoal briquettes in accordance with SNI No.1/6235/2000 standards.   The method used in this research is using experimental method with experimental design using non-factorial Completely Randomized Design (RAL) with three treatments of raw material types with 3 replications.     Based on the results of the study, the following conclusions were obtained: The value of moisture content, ash content, fly substance content and calorific value are included in the SNI 01-6235-2000 standard except the calorific value of corn cob charcoal briquettes is not included in the standard. Bound carbon content is not found in SNI 01-6235-2000 but based on Japanese, American and British standards the value is included in the standard. The highest value of moisture content in corn cob briquettes (TJ) with a value of 0.88% and the lowest in coconut shells at 0.41%.   The highest ash content value in the mixed charcoal briquettes of corn cob and coconut shell (TT) was 11.79% and the lowest in the coconut shell charcoal briquettes (TK) was 7.09%. The highest value of flying matter content in the mixed charcoal briquettes of corn cob and coconut shell (TT) was 25.67% and the lowest in coconut shell (TK) was 10.22%.   The value of bound carbon content of corn cob (TJ) was higher at 77.86% and the lowest in the charcoal briquette of mixed corn cob coconut shell (TT) at 50.94%.   The highest calorific value in the mixed charcoal briquettes of coconut shell corn cob (TT) was 5974 cal/gr and the lowest in the charcoal briquettes of corn cob was 4227 cal/gr.Keywords: charcoal briquette, coconut shell, corn cob, biomassAbstrakLimbah pertanian perlu dilakukan pengolahan menjadi produk yang   memberi manfaat dengan membuat bahan bakar alternative berupa biobriket (briket arang). Tujuan dari penelitian ini mengetahui komposisi terbaik briket arang dari limbah cangkang kelapa dan tongkol jagung dengan melakukan pengujian briket arang agar mendapat briket arang yang berkualitas sesuai dengan standar SNI No.1/6235/2000.   Metode yang digunakan dalam penelitian ini menggunakan metode eksperimen dengan rancangan percobaan menggunakan Rancangan Acak Lengkap (RAL) non faktorial dengan tiga perlakuan jenis bahan baku dengan 3 ulangan.     Berdasarkan hasil penelitian diperoleh beberapa kesimpulan bahwa hasil uji sifat fisis yang terdiri dari nilai kadar air, kadar abu, kadar zat terbang dan nilai kalor sudah memenuhi persyaratan standar SNI 01-6235-2000. Akan tetapi, nilai kalor briket arang tongkol jagung tidak masuk dalam standar. Kadar karbon terikat tidak terdapat pada SNI 01-6235-2000 tetapi berdasarkan standar Jepang, Amerika dan Inggris nilainya masuk dalam standar. Nilai kadar air tertinggi pada briket tongkol jagung (TJ) dengan nilai sebesar 0,88% dan terendah pada cangkang kelapa sebesar 0,41%.   Nilai kadar abu tertinggi pada briket arang campuran tongkol jagung dan cangkang kelapa (TT) sebesar 11,79% dan terendah pada briket arang tempurung kelapa (TK) sebesar 7,09%. Nilai kadar zat terbang tertinggi pada briket arang campuran tongkol jagung tempurung kelapa (TT) sebesar 25,67% dan terendah pada tempurung kelapa (TK) sebesar 10,22%.   Nilai kadar karbon terikat tongkol jagung (TJ) lebih tinggi sebesar 77,86% dan terendah pada briket arang campuran tongkong jagung tempurung kelapa (TT) 50,94%.   Nilai kalor tertinggi pada briket arang campuran tongkol jagung tempurung kelapa (TT) sebesar 5974 cal/gr dan yang terendah pada briket arang tongkol jagung sebesar 4227 cal/grKata kunci: briket arang, tempurung kelapa, bongkol jagung, biomassa